Integrated Analysis Reveals Critical Ferroptosis Regulators and FTL Contribute to Cancer Progression in Hepatocellular Carcinoma - Ke, Shaoying; Wang, Congren; Su, Zijian; Lin, Shaoze; Wu, Gongle (Frontiers in Genetics, 2022)
Background: The carcinogenesis and prognosis of hepatocellular carcinoma (HCC) involve complex molecular mechanisms, and ferroptosis is related to the development and therapeutic efficacy of HCC, but the specific mechanism and prognostic role of ferroptosis-related genes in HCC have not been elucidated. Methods: Differentially expressed gene analysis, Cox regression and unsupervised consensus clustering were applied to identify crucial ferroptosis regulators and establish ferroptosis-related subtypes in HCC. Random forest analysis and survival analysis were adopted to confirm FTL as the hub prognostic and diagnostic ferroptosis regulator in HCC. Results: The ferroptosis-related subtypes based on the crucial prognostic ferroptosis regulators showed that patients in fescluster A had a higher survival probability (P <0.001) and better clinical characteristics than patients in fescluster B in the TCGA-LIHC cohort. Patients with high tumor mutation burden (TMB) in fescluster B presented a significantly poorer prognosis. FTL was the core ferroptosis regulator, and its low expression revealed a significant survival advantage compared with its high expression (P =0.03). The expression and predictive value of FTL were both closely related to the clinical features (p <0.05). Expression of FTL accurately distinguished HCC from normal tissues in the TCGA-LIHC cohort, ICGC cohort and GSE14520 dataset. In addition, higher infiltrating fractions of immune cells, such as activated CD8+ T cells and T follicular T helper cells, mainly enriched immune-related signaling pathways, including the IL2-STAT3 signaling pathway and interferon-gamma response signaling pathway, and higher expression of immune checkpoints, including PDCD1, CTLA4, TIGIT and CD83, were presented in patients with high FTL expression (P<0.05). Patients with high FTL were more sensitive to some targeted drugs, such as cisplatin, dasatinib, and sorafenib, than those with low FTL (P<0.05). A nomogram based on FTL accurately predicted the prognosis of HCC. Further knockdown of FTL was determined to significantly inhibit cell proliferation and migration in HCC. Conclusion: Our study validated ferroptosis-related subtypes and FTL with effective prognostic value in HCC and was beneficial for identifying candidates suitable for targeted drug therapy and immunotherapy, thereby offering further insight into individual treatment strategies to improve disease outcomes in HCC patients.